(untitled) (World Science, 2021)
Objective: To evaluate the effectiveness and safety of a novel intra-articular formulation of hyaluronic acid (HA) to treat athletes with articular lesions. Methods: Multicenter, prospective, interventional, observational study analyzing the clinical evolution of athletes who received 2 or 3 intra-articular injections of HA. The study was scheduled in Visit 1 (week 0), Visit 2 (week 1), Visit 3 (week 2), Visit 4 (week 3), and Visit 5 (end of follow up, week 24). The change in Visual Analog Scale (VAS) of pain and in Knee Injury and Osteoarthritis Outcome Score (KOOS) and the rate of return to physical activity were evaluated upon treatment initiation for up to 24 weeks. The incidence of adverse events was recorded throughout the study. Results: Sixty patients were recruited: 28 (46.7%) in the 2-injection group and 32 (53.3%) in the 3-injection group. Mean VAS gradually decreased across the visits, with statistically significant reductions in both groups from Visit 2 to Visit 3 and to Visit 5 (P < 0.0001). Inter-group differences in the change in VAS from Visit 2 to Visit 5 were statistically comparable (P = 0.8271). At Visit 5, the KOOS of all subscales statistically improved in both treatment groups. At the end of follow-up (Visit 5), 75.9% of patients returned to sport in the overall population. Only one patient reported an adverse event. Conclusion: This novel formulation of HA is effective and safe for at least 24 weeks, resulting in a promising treatment option for athletes with articular lesions.